A forgotten double J stent with encrustation leading to pelvi-ureteric obstruction: A case report - Varshney, Govind; Vikram Singh Chauhan,; Ravindra Srivastava,; Purshotam Dass Gupta,; Shilpi Bhattacharya, (Asian Journal of Medical Sciences, 2024)
Double J (DJ) ureteric stents are widely applied in urological operations, they maintain patient’s urinary system postoperatively, thereby accelerating recovery. Prolonged stent insertion is associated with complications. A 38-year-old woman presented with hematuria, right flank pain, and urinary tract infection. She underwent renal calculi removal 8 years ago. KUB radiograph revealed and indwelling DJ stent with vesical calculus and pyelonephritis. Ultrasound revealed a large bladder stone with mild right hydronephrosis. Computed tomographic (CT) urography revealed a DJ stent encrustation and further formation into core of the bladder stone. Cystolithotomy was performed, vesicle calculi retrieved. At 4 weeks, the patient presented with a right-side flank pain for which patient was evaluated with a contrast-enhanced CT urography which revealed a pelvi-ureteric junction obstruction with hydronephrosis. A pyeloplasty was performed and DJ stent was placed in situ, to be retrieved at 6 weeks. With improved biomaterials, design and technological improvements of DJ stents, patient’s discomfort is greatly reduced. As a result, DJ stents got left in place for a longer duration of time, and therefore high incidences of forgetfulness, retained DJ stents. Encrustation, however, is frequently encountered. Patient factors such as low education and socioeconomic status and patients living in far off rural places also contribute to forgotten indwelling stents. Authors recommend placement of DJ stents after pyeloplasty for treating pelvi-ureteric junction obstructions following long-term retained stents. Patient counseling, education, and strict follow-up should ensure a timely stent removal and improved patient safety. Effective patient counseling and awareness reduces incidences of forgotten indwelling stents and patient-related complications.